The unmaking of Arab socialism - Kadri, Ali (Anthem frontiers of global political economy., 2016)
This study examines the perplexing reasons for the Arab world's developmental descent from the pinnacle of Arab socialism to its present desolate condition, focusing on Egypt, Syria, and Iraq.